Implementasi Enterprise Resource Planning System Odoo Modul Website dalam Melakukan Pemasaran - Patimah, Siti; Ayu, Naia Kusumaning; Hajar, Dewi (MEDIANTARA: Indonesian Journal of Creative Business and Technology (IJCBT), 2025)
This study focuses on the implementation of the Website module in the Odoo Enterprise Resource Planning (ERP) system to support the marketing strategy of the Micro, Small, and Medium Enterprise (MSME) Bakso Krucil Tukuwo. The objective of this research is to develop a technology-based solution capable of enhancing marketing efficiency while effectively managing product information. Using the Rapid Application Development (RAD) methodology, the system development process is carried out rapidly, in a structured manner, and oriented toward user needs. The research stages include user requirement identification, system planning, user interface design, module development, as well as implementation and evaluation. The results of the study indicate that the Website module in Odoo provides various features that support integrated content management, product cataloging, and customer interaction. These features facilitate MSMEs in presenting product information professionally, expanding market reach through digital media, and increasing customer engagement. The developed system not only helps MSMEs market their products more broadly but also reduces operational barriers, such as time-consuming manual information management. Marketing digitalization through this module has proven to enhance efficiency and competitiveness of MSMEs in the era of information technology. This study offers a practical solution for MSMEs to utilize Enterprise Resource Planning (ERP) technology as a tool for digital transformation. The designed website platform enables more modern, organized, and measurable business management. As a result, the system not only supports effective marketing but also opens opportunities for innovation and sustainable growth in the MSME sector.